Jingqianshu granules mitigates premenstrual depression by regulating orexin signaling - Dong, Ping; Dai, Weibo; Zhao, Tingting; Gong, Yuandong; Weng, Ning; Lv, Shimeng; Zhao, Yifan; Du, Chunyu; Ma, Yuexiang; Zhang, Zhen; He, Shuhua; Zheng, Feng; et al. (Frontiers in Pharmacology, 2024)
Introduction: Premenstrual dysphoric disorder (PMDD), a severe form of premenstrual syndrome (PMS), is a serious health disorder that affects patient moods. It is caused by cyclic psychological symptoms and its pathogenesis is still unclear. Abnormalities in the basolateral amygdala (BLA) orexin system, which are important causes of the development of depressive mood, have not been reported in PMDD, so exploring its intrinsic mechanisms is meaningful for enriching the pathomechanisms of PMDD. Methods: High performance liquid chromatography was used for the determination of the active ingredients of Jingqianshu granules. Developing a rat model of premenstrual depression using the forced swimming test (FST). The experiment consisted of two parts. In Part 1, the rats were divided into the control group, the model group, the model + Jingqianshu group, and the model + fluoxetine group. The FST, open field test, and elevated plus maze test, were used to assess the behavior of the rats as well as to evaluate the effect of drug intervention. Immunofluorescence and RT-qPCR were used to detect the expression of orexin and its receptors OX1R and OX2R genes and proteins. The expression of Toll-like receptor 4, nuclear factor kappa-B, tumor necrosis factor-α, interleukin 6, and interleukin-1β in the BLA brain region was detected by Western-Blot. In part 2, the rats were injected intracerebrally with orexin-A. Observe the behavioral activities of rats in the control group, model group, and model+orexin-A group. Immunofluorescence was used to detect microglia in the BLA area of rats, and the expression levels of the above inflammatory factors were detected by Western-Blot. Results: The five components of Jingqianshu granules are: paeoniflorin, erulic acid, liquiritin, hesperidin, and paeonol. During the estrous cycle, rats exhibited depressive-like behavior during the non-receptive phase of the behavioral test, which disappeared during the receptive phase. Immunofluorescence and RT-qPCR showed reduced gene and protein expression of orexin, OX1R, and OX2R in the BLA region of rats in the model group.WB showed elevated levels of inflammatory factors. All returned to control levels after drug treatment. In part 2, injection of orexin-A into the BLA brain region of model rats resulted in reduced immunoreactivity of microglia and decreased expression levels of inflammatory factors. Discussion: Jianqianshu granules can achieve the purpose of treating premenstrual depression by regulating orexin-mediated inflammatory factors, which provides a new idea for further research on the pathogenesis of PMDD. However, the current study is still preliminary and the pathogenesis of PMDD is complex. Therefore, more in-depth exploration is needed.